PENERAPAN ASAS ITIKAD BAIK DALAM PERJANJIAN SIMPAN PINJAM ANTARA KOPERASI UNIT DESA (KUD) DENGAN DEBITUR ( Studi di Koperasi Unit Desa (KUD Pakis) kecamatan Pakis Kabupaten Malang ) - Dicky Agil Bellyangga (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACTThe Government has invented a new way a cooperative model that operates in rural areas (known as Koperasi Unit Desa), which is strengthened by another community empowerment program). This research intends to find out how the principle of good faith was exercised during the formation, implementation, and resolution of bad loans in the funding agreement between Pakis KUD. This research employs juridical and empirical approach which has descriptive characteristic. The data used in this research is obtained from field and literature research which are qualitatively and analyzed afterward. The research shows that, first, the good faith principle in said agreement can be divided into two parts: the good faith principle in the subjective sense— which can be seen in the form of honesty and transparency of the KUD and its members, although it is not always done, and the good faith principle in the objective sense – reflected during the appropriate and rational implementation, but the exercise of good faith is not perfect. Second, the exercise of the good faith principle in the settlement of bad loans in the revolving fund loan agreement can be seen from the process of billing and rescuing revolving fund loans. Keywords: Contract Law, Good Faith, KUD, Loan Lending Agreement